Formation and the structure of freeze-dried MgO nanoparticle foams and their electrical behaviour in polyethylene1. Issue 14 (14th April 2015) - Pallon, L. K. H.; Olsson, R. T.; Liu, D.; Pourrahimi, A. M.; Hedenqvist, M. S.; Hoang, A. T.; Gubanski, S.; Gedde, U. W.
<x xml:space="preserve">Abstract</x> Electrically insulating low-density polyethylene (LDPE) nanocomposites based on dispersed MgO nanoparticle foams are reported.